Factores asociados a la mortalidad en accidentes vehiculares reportados en el distrito de Chao; 2013 – 2016 - Sare Lara, Evergisto (2018)
The purpose of this research is to determine the factors associated with mortality in vehicular accidents reported in the Chao district; 2013-2016. Measurements made by the National Police of Peru in the jurisdiction of the Chao district were used, it was constituted by 257 records of vehicular accidents and the mythology of the binary logistic regression analysis was used. Obtaining the model of binary logistic regression "model2", significant (sig = 0.000), explains 27% (R squared of Nagelkerke) of the variance of the dependent variable. The hosmer and lemeshow test is significant (sig = 0.407). The model correctly classifies 86% of the cases. The Wald statistic (sig <0.05) indicates that the coefficients of the independent variables contribute significantly to the prediction of the dependent variable; therefore, the results obtained can be generalized to the population. It is concluded that the factors associated with mortality in vehicular accidents in Chao district, according to the binary logistic regression model, are: alcohol, excessive speed, recklessness of the driver, place of occurrence, type of vehicle and time slot